Analysis of Physical, Chemical and Biological Aspects of Drinking Water at University of Sindh Jamshoro: Short Communication - Jabeen, Shagufta; Naz, Humaira; Kumari, Nimerta; Naz, Shaista (International Journal of Economic and Environmental Geology, 2022)
Safe drinking water is a basic need for good health. It is critically needed to characterize drinking water, by measuring its pH and electrical conductivity, total dissolved solids, and analysing for biological contamination. Drinking water quality standards are set with some parameters and that harmful constituents should not exveed (WHO guidelines (2011).